2016
DOI: 10.1371/journal.pone.0148478
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Domain Vc1 Regulates Downstream Gene Expression in Response to Cyclic Diguanylate in Vibrio cholerae

Abstract: In many bacterial species, including the aquatic bacterium and human pathogen Vibrio cholerae, the second messenger cyclic diguanylate (c-di-GMP) modulates processes such as biofilm formation, motility, and virulence factor production. By interacting with various effectors, c-di-GMP regulates gene expression or protein function. One type of c-di-GMP receptor is the class I riboswitch, representatives of which have been shown to bind c-di-GMP in vitro. Herein, we examined the in vitro and in vivo function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…As a result, its physiological role in V. cholerae c-di-GMP regulation remains undefined. A related class I riboswitch in V. cholerae, termed Vc1, was recently shown to regulate the surface binding protein GbpA, functioning as an on switch in response to c-di-GMP (20).…”
mentioning
confidence: 99%
“…As a result, its physiological role in V. cholerae c-di-GMP regulation remains undefined. A related class I riboswitch in V. cholerae, termed Vc1, was recently shown to regulate the surface binding protein GbpA, functioning as an on switch in response to c-di-GMP (20).…”
mentioning
confidence: 99%
“…In addition, the presence of a large set of genes regulated (both positively and negatively) by c-di-GMP riboswitches provides the opportunity to examine the differences in responsiveness of this class of c-di-GMP receptor to changes in intracellular c-di-GMP. For example, differences between riboswitches of the same type may result in changes to ligand affinity, resulting in responses to different threshold concentrations of c-di-GMP ( 20 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Initial transcriptional analyses indicated that class II riboswitches are uniformly “on” switches, while all but one class I riboswitch are “off” switches in response to c-di-GMP in C. difficile . However, there are multiple examples of ligands also affecting the activity of the promoter upstream of their cognate riboswitch ( 39 , 40 , 48 , 49 ). For example, in vivo studies of class I c-di-GMP riboswitches in Vibrio cholerae , Vc1 and Vc2, showed that c-di-GMP regulates the expression the downstream genes gbpA and tfoY at two levels: by controlling transcription initiation via the upstream promoters and via the riboswitches ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations